A sense of urgency - Kotter, John P., 1947- (Boston, Mass. : Harvard Business Press, 2008)
In his international bestseller "Leading Change," Kotter provided an action plan for implementing successful transformations. Now, he shines the spotlight on the crucial first step in his framework: creating a sense of urgency by getting people to actually see and feel the need for change.
It all starts with a sense of urgency -- Complacency and false urgency -- Increasing true urgency: one strategy, four tactics -- Tactic one: bring the outside in -- Tactic two: behave with urgency every day -- Tactic three: find opportunity in crises -- Tactic four: deal with NoNos -- Keeping urgency up -- The future: begin today.
Description based on print version record.
Keywords: Organizational change; Organization -- Management; Leadership; Personnel management; Change Management; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books